Towards an emancipation of patients : patients' experience and the patient movement - Williamson, Charlotte, 1932- (Policy, 2010)
The patient movement works to improve the quality of healthcare. Some of the work entails trying to get standards of care that put patients at institutionalised disadvantage replaced by standards that free (emancipate) patients from that disadvantage. Combining new academic theory with rich empirical evidence, the author explains how looking at healthcare from an emancipatory perspective could improve its quality as patients experience it.